Lithium ion battery flame-retardant electrolyte and preparation method and application thereof
By using bistrifluoromethanesulfonimide salt and fluorinated phosphazene flame retardant in lithium-ion battery electrolyte, combined with lithium hexafluorophosphate, the problems of insufficient flame retardant performance and cycle stability of the battery are solved, and the rate performance of the battery is improved and security.
Patent Information
- Application Number
- CN202411152957.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-21
AI Technical Summary
The flame retardant performance of existing lithium-ion battery electrolytes is insufficient, resulting in high fire risk, and the increase of high boiling point solvents and flame retardant additives will lead to battery internal resistance and cycle stability problems.
Bistrifluoromethanesulfonimide salt additives are used, combined with lithium hexafluorophosphate and fluoride phosphazene flame retardant, to control the viscosity of the electrolyte and improve the migration number of lithium ions, and enhance the rate performance and cycle stability of the battery.
It realizes the high-rate performance and cycle stability of the battery, and at the same time improves the flame retardant performance of the electrolyte, shortens the self-extinguishing time, and ensures the safety and performance of the battery.
Smart Images

Figure CN119133602A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a flame retardant electrolyte for lithium ion batteries and a preparation method and application thereof. Background Art
[0002] Lithium battery electrolyte is a key material in lithium-ion batteries, equivalent to the "blood" of lithium-ion batteries, and determines the key performance of lithium batteries. Improving the flame retardant properties of lithium-ion battery electrolytes is conducive to improving the safety of terminal products such as power vehicles, digital 3C, and energy storage power stations, and can prevent property losses and personal injuries caused by fires caused by battery rupture or accidental short circuits.
[0003] At present, the electrolyte of lithium-ion batteries is usually an organic system, and the commonly used solvents for the electrolyte are alkyl carbonate compounds. Chain carbonates usually use ethylene carbonate (EC) and propylene carbonate (PC), and linear carbonates usually use dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). These solvents have very low flash points, especially chain carbonate solvents, so lithium-ion battery electrolytes are extremely flammable.
[0004] In order to improve the safety of lithium-ion batteries, common work carried out in the electrolyte safety aspect includes: using high-boiling point solvents such as γ-butyrolactone, certain sulfone solvents, and even using a large amount of propylene carbonate. However, these high-boiling point solvents only have non-flammable properties and cannot provide flame retardant properties. Moreover, their use will result in higher viscosity, such as γ-butyrolactone (viscosity 1.5 mPa·s), while the viscosity of the more viscous hexafluorocyclotriphosphazene is only 1.2 mPa·s at the same temperature. Moreover, the amount of high-boiling point solvent used is much higher than the amount of additives used. Therefore, the use of the above-mentioned high-boiling point solvents will result in higher viscosity, which will seriously affect the rate performance of the battery and increase the internal resistance of the battery.
[0005] Some flame retardant additives have also emerged, especially phosphates. Currently commonly used flame retardant additives include trimethyl phosphate (TMP), triethyl phosphate (TEP), dimethyl methyl phosphate (DMMP), triphenyl phosphate (TPP), etc. The addition of an appropriate amount can shorten the self-extinguishing time of the electrolyte, but it is not compatible with the graphite negative electrode and cannot form a stable SEI film. Therefore, the electrolyte containing the above additives cannot guarantee the cycle stability of the battery.
[0006] In recent years, fluorinated phosphazene flame retardants have been used in electrolytes to a certain extent. Because they are rich in phosphorus, nitrogen and fluorine elements, the synergistic effect between the three greatly improves the flame retardant properties of the electrolyte. At the same time, fluorinated phosphazene flame retardants can generate LiF-rich SEI film at the negative electrode, and generate alkyl-substituted phosphazenes that migrate to the positive electrode and participate in the positive electrode film formation.
[0007] In order to ensure stable safety during cycling, the actual addition amount of fluorinated phosphazenes in carbonate electrolytes is usually between 5-15%. Although the flame retardant properties of the electrolyte are ensured, the fluorinated phosphazene additives have high viscosity. For example, the viscosity of hexafluorocyclotriphosphazene is 1.2 mPa·s at room temperature, which causes a decrease in battery rate performance and affects the promotion of this commercial solution. Summary of the invention
[0008] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and provide a flame retardant electrolyte for lithium ion batteries and a preparation method and application thereof. By adding bis(trifluoromethanesulfonyl)imide salt additives, while ensuring the flame retardant performance of the electrolyte, the migration number of lithium ions is effectively increased, the rate performance of the battery is improved, and at the same time, it combines with the anions in the lithium salt to improve the cycle stability of the battery.
[0009] In order to achieve the above technical effects, the present invention adopts the following technical solutions:
[0010] A flame retardant electrolyte for lithium ion batteries, comprising a non-aqueous solvent, a lithium salt, a flame retardant and a bis(trifluoromethanesulfonyl)imide salt, wherein the lithium salt is selected from lithium hexafluorophosphate (LiPF 6 ) or lithium bis(trifluoromethanesulfonyl)imide (LiFSI), the flame retardant is a fluorinated phosphazene organic substance, the flame retardant accounts for 0.5wt%-20wt% of the total mass of the electrolyte, and the bis(trifluoromethanesulfonyl)imide salt is selected from any one of the compounds shown in the following formula:
[0011]
[0012]
[0013] Among them, R 1 -R 11 They are all alkyl groups with 1 to 4 carbon atoms, and the flame retardant and the bis(trifluoromethanesulfonyl)imide salt together account for 3wt% to 20wt% of the total mass of the electrolyte.
[0014] Fluorinated phosphazene additives are a commonly used flame retardant additive, but their large-scale addition will cause the problem of reduced rate performance of the electrolyte due to excessive viscosity. Adding bis(trifluoromethanesulfonyl imide) salts to the electrolyte can effectively reduce the amount of phosphazenes used to control the viscosity of the electrolyte and increase the ion migration number to improve the rate performance of the electrolyte. At the same time, the cationic part of the bis(trifluoromethanesulfonyl imide) salt can also provide water and acid removal effects to further improve the cycle stability of the battery. Other additives in the electrolyte are commonly used film-forming additives, which mainly ensure the cycle stability of the battery.
[0015] The flame retardant electrolyte for lithium ion batteries provided by the present invention introduces bis(trifluoromethanesulfonyl)imide salt, wherein the bis(trifluoromethanesulfonyl)imide anion is The bis(trifluoromethanesulfonyl)imide group has a larger anion radius, which effectively increases the number of lithium ion migration in the electrolyte, thereby improving the battery rate performance. Furthermore, when lithium hexafluorophosphate is used as the lithium salt, the cation in the bis(trifluoromethanesulfonyl)imide salt is a Lewis acid, which can react with the Lewis base Combined to prevent the former from decomposing into HF and This effectively improves the cycle stability of the battery. At the same time, bis(trifluoromethanesulfonyl)imide salt is also rich in N, P and F elements, which can further improve the flame retardant properties of the electrolyte.
[0016] Preferably, the lithium salt is lithium hexafluorophosphate.
[0017] Preferably, the non-aqueous solvent is selected from at least two of carbonates such as ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate and carboxylates such as ethyl acetate, propyl acetate, propyl propionate, methyl propionate and the like; further preferably, the non-aqueous solvent accounts for 60wt%-90wt% of the total mass of the electrolyte.
[0018] Preferably, the lithium salt accounts for 8.0 wt%-18.0 wt% of the total mass of the electrolyte.
[0019] Preferably, the flame retardant electrolyte for lithium-ion batteries also includes additives, and the additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sultone, lithium difluorophosphate, vinyl sulfate, and methylene disulfonate; further preferably, the additives account for 0.5wt%-10wt% of the total mass of the electrolyte.
[0020] Preferably, the flame retardant electrolyte of the lithium ion battery has a thermal conductivity of ≤4.5s·g -1 The self-extinguishing time.
[0021] The present invention also provides a method for preparing the flame-retardant electrolyte for lithium-ion batteries, wherein a non-aqueous solvent is mixed in a glove box filled with argon gas, a flame retardant, a bis(trifluoromethanesulfonyl)imide salt and an additive are added to the non-aqueous solvent and mixed, and then a lithium salt is slowly added to the mixed solution, and the flame-retardant electrolyte for lithium-ion batteries is obtained after stirring. Preferably, the moisture content in the glove box components is less than 1 ppm, and the oxygen content is less than 1 ppm.
[0022] The present invention also provides the use of the flame retardant electrolyte for lithium ion batteries or the flame retardant electrolyte for lithium ion batteries prepared by the above preparation method as an electrolyte in the preparation of lithium ion batteries.
[0023] Preferably, a lithium ion battery made from a flame retardant electrolyte for lithium ion batteries is placed in a constant temperature box at 25°C, charged to 4.5V at a constant current and voltage of 1C, with a cut-off current of 0.05C, and discharged to 3.0V at a constant current of 1C. The capacity retention rate after 500 cycles is in the range of 80.5%-83.5%.
[0024] Beneficial effects of the present invention:
[0025] 1. The flame retardant electrolyte for lithium ion batteries provided by the present invention is obtained by introducing bis(trifluoromethanesulfonyl)imide salt, wherein the bis(trifluoromethanesulfonyl)imide anion is The bis(trifluoromethanesulfonyl)imide group has a larger anion radius, which effectively increases the number of lithium ion migration in the electrolyte, thereby improving the battery rate performance. When lithium hexafluorophosphate is used as the lithium salt, the cation in the bis(trifluoromethanesulfonyl)imide salt is a Lewis acid, which can react with the Lewis base Combined to prevent the former from decomposing into HF and This effectively improves the cycle stability of the battery. At the same time, bis(trifluoromethanesulfonyl)imide salt is also rich in N, P and F elements, which can further improve the flame retardant properties of the electrolyte.
[0026] 2. The flame retardant electrolyte for lithium-ion batteries provided by the present invention has a maximum of 4.5s·g -1 After the battery is prepared, it is placed in a constant temperature box at 25°C, charged to 4.5V at a constant current and constant voltage of 1C, the cut-off current is 0.05C, and discharged to 3.0V at a constant current of 1C. The capacity retention rate of 500 cycles is in the range of 80.5%-83.5%. DETAILED DESCRIPTION
[0027] The present invention will be further described below with reference to the embodiments and comparative examples.
[0028] The reagents and experimental equipment used in the examples and comparative examples are all commercially available common reagents and experimental equipment in the art, and their specific sources are not described in detail here.
[0029] The present invention provides a flame retardant electrolyte for lithium ion batteries, comprising a non-aqueous solvent, a lithium salt, a flame retardant and a bis(trifluoromethanesulfonyl)imide salt, wherein the lithium salt is selected from lithium hexafluorophosphate (LiPF4 6 ) or lithium bis(trifluoromethanesulfonyl)imide (LiFSI), the flame retardant is a fluorinated phosphazene organic substance, and the bis(trifluoromethanesulfonyl)imide salt is selected from any one of the compounds shown in the following formula:
[0030]
[0031] Among them, R 1 -R 11They are all alkyl groups with 1 to 4 carbon atoms, and the flame retardant and the bis(trifluoromethanesulfonyl)imide salt together account for 3wt% to 20wt% of the total mass of the electrolyte.
[0032] Preferably, the lithium salt is lithium hexafluorophosphate.
[0033] Preferably, the non-aqueous solvent is selected from at least two of carbonates such as ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate and carboxylates such as ethyl acetate, propyl acetate, propyl propionate, methyl propionate and the like; further preferably, the non-aqueous solvent accounts for 60wt%-90wt% of the total mass of the electrolyte.
[0034] Preferably, the lithium salt accounts for 8.0wt%-18.0wt% of the total mass of the electrolyte, and the molar concentration of the lithium salt is 1.0M-1.3M.
[0035] Preferably, the flame retardant electrolyte for lithium-ion batteries also includes additives, and the additives are selected from at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sultone, lithium difluorophosphate, vinyl sulfate, and methylene disulfonate; further preferably, the additives account for 0.5wt%-10wt% of the total mass of the electrolyte.
[0036] The flame retardant electrolyte for lithium ion batteries provided in each embodiment is prepared by the following method:
[0037] In a glove box filled with argon (water <1ppm, oxygen <1ppm), the non-aqueous solvent is mixed, a flame retardant, bis(trifluoromethanesulfonyl)imide salt and an additive are added to the non-aqueous solvent and mixed, and then lithium salt is slowly added to the mixed solution. After stirring evenly, a flame retardant electrolyte for lithium-ion batteries is obtained.
[0038] The preparation methods of the flame-retardant electrolytes for lithium-ion batteries provided in the comparative examples are different from those in the examples in that no bis(trifluoromethanesulfonyl)imide salt is added.
[0039] The component contents of the flame retardant electrolytes for lithium ion batteries provided in the embodiments and comparative examples are shown in the following table:
[0040] Table 1 Component content
[0041]
[0042]
[0043] Experimental Example 1
[0044] Self-extinguishing time (SET) test
[0045] A spherical core with a diameter of 0.3-0.5 cm absorbs 0.05-0.10 g of electrolyte, and then the extinguishing time is standardized according to the sample weight. The results are divided into three categories: if SET < 6 s g -1 , the electrolyte is considered "non-flammable"; such as 6s·g -1 <SET<20s·g -1 , considered as "flame retardant"; if SET>20s·g -1 , considered as "flammable". The electrolytes prepared in the comparative example and the embodiment were tested in the above manner to obtain the self-extinguishing time data. The test results are shown in Table 2
[0046] Table 2 Self-extinguishing time
[0047]
[0048]
[0049] Unignitable: This is mainly because the electrolyte has too much flame retardant added, so it cannot be ignited. Usually, the amount of flame retardant added is greater than 10wt%, and the phenomenon of unignitability occurs; the self-extinguishing time is also related to the amount added and the solvent. The higher the amount of flame retardant additive added, the shorter the self-extinguishing time. At the same time, the addition of the above-mentioned bis(trifluoromethanesulfonyl)imide salt will also reduce the self-extinguishing time. The higher the amount added, the shorter the self-extinguishing time.
[0050] Experimental Example 2
[0051] Battery performance test
[0052] In a glove box filled with argon (water <1 ppm, oxygen <1 ppm), the lithium battery electrolytes prepared in Comparative Examples 1-6 and the lithium ion battery electrolytes prepared in Examples 1-10 were injected into the positive electrode, which was lithium cobalt oxide, and the negative electrode, which was artificial graphite (90%) and SiO X (10%) soft pack battery, the rated capacity of the battery is 1mAh, the battery is tested for normal temperature cycle performance, the specific test method is as follows:
[0053] The battery was placed in a constant temperature box at 25°C, and charged to 4.5V at a constant current and constant voltage of 1C, with a cut-off current of 0.05C, and then discharged to 3.0V at a constant current of 1C. This cycle was repeated for 500 weeks, and the discharge capacity of the first week and the discharge capacity of the 500th week were recorded. The capacity retention rate was calculated according to the following formula: 1C = 1mA.
[0054] The test results are shown in Table 3.
[0055] Table 3 Capacity retention rate
[0056] Group 500 cycles capacity retention rate Comparative Example 1 76.8% Comparative Example 2 77.2% Comparative Example 3 78.2% Comparative Example 4 77.9% Comparative Example 5 76.5% Comparative Example 6 77.8% Example 1 81.2% Example 2 80.7% Example 3 80.5% Example 4 83.2% Example 5 82.8% Example 6 81.5% Example 7 82.9% Example 8 82.7% Example 9 81.8% Example 10 83.5%
[0057] In Table 3, the calculation method of 500-cycle capacity retention rate is as follows:
[0058] 500-cycle capacity retention rate (%) = (500th cycle discharge capacity / 1st cycle discharge capacity) × 100%.
[0059] Compared with the comparative example, the embodiment greatly improves the cycle stability of the battery mainly due to the dehydration and acid removal functions of the bis(trifluoromethanesulfonic acid) imide salt.
[0060] Similarly, because the amount of film-forming additives added is different from that of the above-mentioned additives, it also has a certain impact on the cycle stability of the battery. It basically follows the trend that within a reasonable range, the higher the amount added, the better the cycle stability.
[0061] Experimental Example 3
[0062] Rate performance test
[0063] The battery prepared in Experimental Example 2 was charged to 4.5 V using 0.5C / 1.0C / 3C / 5C currents, charged at a constant voltage to a current of 0.05C, and discharged using 0.5C / 1.0C / 3C / 5C. Ten cycles were cycled at each current density, and the discharge capacity of the fifth cycle at each current density was recorded.
[0064] The test results are shown in Table 4.
[0065] Table 4 Discharge capacity data
[0066] Group 0.5C 1C 2C 5C Comparative Example 1 1102.2mAh 1070.5mAh 910.9mAh 640.8mAh Comparative Example 2 1097.5mAh 1053.5mAh 912.3mAh 668.1mAh Comparative Example 3 1098.8mAh 1075.2mAh 885.3mAh 620.8mAh Comparative Example 4 1102.4mAh 1078.5mAh 930.5mAh 685.3mAh Comparative Example 5 1100.5mAh 1058.5mAh 918.3mAh 675.1mAh Comparative Example 6 1102.5mAh 1056.5mAh 915.3mAh 672.6mAh Example 1 1115.6mAh 1088.4mAh 950.2mAh 680.8mAh Example 2 1123.5mAh 1095.4mAh 965.5mAh 700.4mAh Example 3 1125.3mAh 1099.2mAh 967.4mAh 702.5mAh Example 4 1130.8mAh 1100.5mAh 970.8mAh 715.1mAh Example 5 1125.3mAh 1089.8mAh 935.0mAh 688.5mAh Example 6 1128.2mAh 1086.2mAh 932.4mAh 690.3mAh Example 7 1133.5mAh 1105.6mAh 982.2mAh 720.2mAh Example 8 1135.5mAh 1120.6mAh 987.7mAh 728.3mAh Example 9 1127.8mAh 1108.5mAh 979.8mAh 720.1mAh Example 10 1125.8mAh 1106.5mAh 975.8mAh 718.6mAh
[0067] The reason why Comparative Example 4 has the best performance: Compared with Comparative Example 4, Comparative Example 1 has a lower lithium salt concentration and a lower ion conductivity, so the rate performance is poor. Compared with Comparative Example 4, Comparative Example 3 has a higher amount of flame retardant additives added and a large electrolyte viscosity, which leads to poor rate performance. Compared with Comparative Example 2, Comparative Example 4 has better electrolyte conductivity and viscosity than Comparative Example 2 mainly because of the above-mentioned carboxylic acid ester additives, so the rate performance is better than Comparative Example 2.
[0068] Compared with Comparative Example 1, Examples 1 and 2 mainly increase the number of lithium ion migration and thus improve the rate performance of the battery due to the addition of the above-mentioned bis(trifluoromethanesulfonyl)imide salt additive.
[0069] Compared with Comparative Example 2, Examples 3 and 4 also increase the number of lithium ion migrations due to the addition of the above-mentioned bis(trifluoromethanesulfonyl)imide salt additive, thereby improving the battery rate performance. The comparison between Examples 3 and 4 is mainly due to the fact that the amount of bis(trifluoromethanesulfonyl)imide lithium salt additive is larger, so Example 4 has better performance.
[0070] Compared with Comparative Example 3, Examples 5 and 6 also have improved rate performance due to the introduction of bis(trifluoromethanesulfonyl)imide lithium salt. Compared with other examples, the poor performance is caused by the high viscosity of the electrolyte caused by excessive addition of flame retardant additives. The comparison between Examples 5 and 6 is mainly due to the fact that the amount of bis(trifluoromethanesulfonyl)imide lithium salt added is larger, so Example 6 has better performance.
[0071] Compared with Comparative Example 4, Examples 7 and 8 also have improved rate performance due to the introduction of bis(trifluoromethanesulfonyl)imide lithium salt. The better performance compared with other examples is due to the introduction of carboxylic acid ester solvents, which have lower viscosity than carbonate, thereby improving the overall rate performance.
[0072] Comparative Examples 5 and 6 are compared with Comparative Example 2. The reason for the decrease in cycle stability in Comparative Example 5 is mainly because the simple lithium bis(fluorosulfonyl)imide is a lithium salt that corrodes the current collector, resulting in a certain decrease in cycle stability. In Comparative Example 6, due to the presence of lithium hexafluorophosphate, it can passivate the current collector, so that the cycle stability is not affected. Also, because the anion radius of lithium bis(fluorosulfonyl)imide is larger than that of lithium hexafluorophosphate, the ion migration number is improved to a certain extent, thereby improving the rate performance. The reason why the rate performance of Examples 9 and 10 is superior to that of Comparative Example 4 is consistent with the above reasons.
Claims
1. A flame retardant electrolyte for lithium ion batteries, It is characterized in that The invention comprises a non-aqueous solvent, a lithium salt, a flame retardant and a bis(trifluoromethanesulfonyl)imide salt, wherein the lithium salt is selected from lithium hexafluorophosphate or lithium bis(fluorosulfonyl)imide, the flame retardant is a fluorinated phosphazene organic substance, and the flame retardant accounts for 0.5wt%-20wt% of the total mass of the electrolyte. The bis(trifluoromethanesulfonyl)imide salt is selected from any one of the compounds represented by the following formula: Among them, R 1 -R 11 are all alkyl groups having 1 to 4 carbon atoms, The flame retardant and the bis(trifluoromethanesulfonyl)imide salt together account for 3wt%-20wt% of the total mass of the electrolyte.
2. The flame retardant electrolyte for lithium ion batteries according to claim 1, It is characterized in that The lithium salt is lithium hexafluorophosphate.
3. The flame retardant electrolyte for lithium ion batteries according to claim 1, It is characterized in that The non-aqueous solvent is selected from at least two of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl acetate, propyl acetate, propyl propionate or methyl propionate; further preferably, the non-aqueous solvent accounts for 60wt%-90wt% of the total mass of the electrolyte.
4. The flame retardant electrolyte for lithium ion batteries according to claim 1, It is characterized in that The lithium salt accounts for 8.0wt%-18.0wt% of the total mass of the electrolyte.
5. The flame retardant electrolyte for lithium ion batteries according to claim 1, It is characterized in that The flame retardant electrolyte of the lithium ion battery also includes an additive, which is selected from at least one of vinylene carbonate, fluoroethylene carbonate, 1,3-propylene sultone, lithium difluorophosphate, vinyl sulfate or methylene disulfonate; further preferably, the additive accounts for 0.5wt%-10wt% of the total mass of the electrolyte.
6. The flame retardant electrolyte for lithium ion batteries according to claim 1, It is characterized in that Lithium-ion battery flame retardant electrolyte has a value of ≤4.5s·g -1 The self-extinguishing time.
7. The method for preparing a flame retardant electrolyte for lithium ion batteries according to any one of claims 1 to 6, It is characterized in that In a glove box filled with argon, the non-aqueous solvent is mixed, a flame retardant, bis(trifluoromethanesulfonyl)imide salt and an additive are added to the non-aqueous solvent and mixed, and then lithium salt is slowly added to the mixed solution. After stirring evenly, a flame retardant electrolyte for lithium-ion batteries is obtained.
8. The preparation method according to claim 7, It is characterized in that The moisture content in the glove box components is less than 1ppm and the oxygen content is less than 1ppm.
9. Use of the flame retardant electrolyte for lithium ion batteries as claimed in any one of claims 1 to 6 or the flame retardant electrolyte for lithium ion batteries prepared by the preparation method as claimed in any one of claims 7 to 8 as an electrolyte in the preparation of lithium ion batteries.
10. The use according to claim 9, It is characterized in that The lithium-ion battery made of lithium-ion battery flame-retardant electrolyte was placed in a constant temperature box at 25°C, charged to 4.5V at a constant current and voltage of 1C, with a cut-off current of 0.05C, and discharged to 3.0V at a constant current of 1C. The capacity retention rate after 500 cycles was in the range of 80.5%-83.5%.
Citation Information
Patent Citations
Phosphazene flame retardant, preparation method thereof and lithium-ion battery electrolyte
CN102916222A
Lithium ion battery electrolyte and lithium ion battery
CN112271328A
Flame retardant nonaqueous electrolyte and secondary battery using it
JP1999329495A
Lithium-ion battery electrolyte and lithium-ion battery
WO2024114166A1
